miR‐1249‐3p accelerates the malignancy phenotype of hepatocellular carcinoma by directly targeting HNRNPK - Hongchun Shu; Jia Hu; Huiqiu Deng (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background microRNAs (miRNAs) have been implicated to play crucial roles in carcinogenesis. miR‐1249‐3p was reported to be abnormally expressed in multiple human cancers. However, its biological role and the associated underlying mechanisms in hepatocellular carcinoma (HCC) remain largely unknown. Methods miR‐1249‐3p expression level in HCC cell lines and normal cell line was measured by quantitative real‐time PCR. Role of miR‐1249‐3p on HCC cell proliferation, colony formation, and invasion was examined by cell counting kit‐8 assay, colony formation assay, and transwell invasion assay, respectively. Luciferase activity reporter assay and western blot were performed to validate whether heterogeneous nuclear ribonucleoprotein K (HNRNPK) was a direct target of miR‐1249‐3p. Effect of miR‐1249‐3p on overall survival of HCC patients was analyzed at KM Plotter website. Results We found miR‐1249‐3p expression level was increased, while HNRNPK expression level was decreased in HCC cell lines compared with normal cell line. Knockdown miR‐1249‐3p expression inhibits HCC cell proliferation, colony formation, and cell invasion through regulating HNRNPK in vitro. We also showed high miR‐1249‐3p expression was a predictor for poor overall survival of HCC patients. Conclusions These findings about miR‐1249‐3p/HNRNPK pair provide a novel therapeutic method for HCC patients.